Genomic Analyses And Characterization On The Temporal And Quantitative Fates Of Human Dna After Blood Meals Of Tropical Bed Bug, Cimex Hemipterus (F.) - Lim, Li (2023)
This research exploits the potential of Cimex hemipterus (F.) as a blood-feeding insect in forensics and also studies the draft genome, metagenome and transcriptome of this species.